A comparison of the Dobbs method for correction of idiopathic and teratological congenital vertical talus. (April 2016) - Chan, Yuen; Selvaratnam, Veenesh; Garg, Neeraj
Abstract: Introduction: Congenital vertical talus (CVT) is a rare deformity. Traditionally, CVT correction involved extensive soft tissue releases, and this was associated with high complication rates. The Dobbs method is less invasive and comprises serial manipulation and casting, followed by minimally invasive reduction and K-wire fixation of the talonavicular joint and percutaneous Achilles tenotomy. Aim: The purpose of our study was to compare the outcomes of using the Dobbs method for CVT correction in idiopathic and teratological patients. Methods: A retrospective analysis of all patients treated with the Dobbs method for CVT between the years 2007 and 2012 was carried out. Notes, electronic records and radiographs were reviewed for every patient. The Oxford ankle foot score was obtained at follow-up. Results: There was a total of ten children with 18 affected feet. Five children (ten feet) had teratological CVT. Recurrence was noted in six feet (two from the idiopathic group and four from the teratological group). The median age was 5 months (range 2–8 months). The mean follow-up was 53 months (range 24–80 months). There was a significant difference between pre-operative to initial post-operative and pre-operative to latest follow-up measurements for all angles in the successfully treated CVT group ( p < 0.000001). The mean Oxford ankle foot scores for each domain in all patients are 59.9 (physical), 88.8 (school and play) and 99.1 (emotional). Conclusion: The Dobbs method is a less invasive technique of CVT correction. It is an effective initial method of treatment in both teratological and idiopathic patients. A higher recurrence rate was observed in the teratological group, although this was not statistically significant.